Perlindungan Hukum Terhadap Konsumen (Studi Kasus Informasi Flash Sale Menyesatkan Bagi Konsumen) - Nilam Cahya, Ayuni; Adi Sudiro, Amoury (UNES Law Review, 2024)
Consumer protection in online transactions and fraud that occurs on marketplace platforms is very important. Protecting consumers from unclear or incorrect information is critical in today's digital environment. In Indonesia, laws already exist to protect consumers. Article 8 of Law Number 8 of 1999 concerning Consumer Protection provides a legal basis for protecting consumers from detrimental business practices. However, in the context of e commerce, more specific regulatory updates and adjustments are needed due to the tendency for fraud and unclear information on online platforms. Governments, police, and marketplace platform providers have an important role to play in educating consumers, enforcing laws regarding violations, and developing stronger policies to protect users. Prevention efforts must also be increased, for example by strengthening seller verification processes, increasing transparency of product information, and improving mechanisms for reporting and handling consumer complaints. The normative juridical research you carry out will make a significant contribution in understanding the need for more specific legal improvements related to electronic transactions and consumer protection on marketplace platforms. This will support efforts to prevent and overcome online fraud which harms consumers.